2014
DOI: 10.1097/nnr.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length

Abstract: Background The exciting discovery that telomere shortening is associated with many health conditions, and that telomere lengths can be altered in response to social and environmental exposures, has underscored the need for methods to accurately and consistently quantify telomere length. Objectives The purpose of this paper is to provide a comprehensive summary that compares and contrasts the current technologies used to assess telomere length. Discussion Multiple methods have been developed for the study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(143 citation statements)
references
References 52 publications
(70 reference statements)
1
141
0
1
Order By: Relevance
“…Methodological differences between studies, as well as many studies with small sample sizes, make conclusions difficult to draw. Although the reasons for the discrepancies between studies are unknown, possibilities include different subject demographics (e.g., age, gender, race, socioeconomic status, history of childhood adversity (O'Donovan et al, 2011a; Price et al, 2013)), different study designs, differences in duration or severity of the investigated illness (Wolkowitz et al, 2011a), different specimen processing and assay protocols (Aviv et al, 2006; Montpetit et al, 2014; Nieratschker et al, 2013) and, importantly, differences in moderators of LTL and PBMC basal TA that are often not assessed, e.g., genetic risk-alleles (Armanios and Blackburn, 2012; Codd et al 2013), including ApoE status (Jacobs et al, 2013; Takata et al, 2012; Wikgren et al, 2012a), cognitive threat appraisal (O'Donovan et al, 2012), pessimistic outlook (O'Donovan et al, 2009), arousal and regulatory system activation (Epel, 2009) and stress resiliency factors (Puterman et al, 2013). For example, recent data suggest that “high risk” genetic polymorphisms in the serotonin and dopamine systems may interact with early life adversity to affect adult LTL (Mitchell et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodological differences between studies, as well as many studies with small sample sizes, make conclusions difficult to draw. Although the reasons for the discrepancies between studies are unknown, possibilities include different subject demographics (e.g., age, gender, race, socioeconomic status, history of childhood adversity (O'Donovan et al, 2011a; Price et al, 2013)), different study designs, differences in duration or severity of the investigated illness (Wolkowitz et al, 2011a), different specimen processing and assay protocols (Aviv et al, 2006; Montpetit et al, 2014; Nieratschker et al, 2013) and, importantly, differences in moderators of LTL and PBMC basal TA that are often not assessed, e.g., genetic risk-alleles (Armanios and Blackburn, 2012; Codd et al 2013), including ApoE status (Jacobs et al, 2013; Takata et al, 2012; Wikgren et al, 2012a), cognitive threat appraisal (O'Donovan et al, 2012), pessimistic outlook (O'Donovan et al, 2009), arousal and regulatory system activation (Epel, 2009) and stress resiliency factors (Puterman et al, 2013). For example, recent data suggest that “high risk” genetic polymorphisms in the serotonin and dopamine systems may interact with early life adversity to affect adult LTL (Mitchell et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Important caveats must be considered in interpreting LTL (Aviv et al, 2006; Epel, 2012), e.g., (a) distinguishing between telomere shortening in the individual leukocyte vs. “apparent” telomere shortening when examining average LTL, due to a re-distribution of leukocyte cell types having different telomere lengths, such as naïve vs. memory T cells; (b) the relationship of LTL to TL in other tissues has not been well established, and TL varies by tissue (although TL is generally positively correlated across certain, but not all, tissues within individuals) (Daniali et al, 2013; Dlouha et al, 2014; Friedrich et al, 2000; Gadalla et al, 2010; Lukens et al, 2009; Mitchell et al, 2014; Nakamura et al, 2002; Takubo et al, 2002; Takubo et al, 2010; Thomas et al, 2008); (c) different results may derive from different DNA extraction and assay methods and different laboratories (Aubert et al, 2012; Aviv et al, 2011; Cunningham et al, 2013; Montpetit et al, 2014; Nieratschker et al, 2013); and (d) even slight DNA degradation can yield spurious TL measuements (Dlouha et al, 2014). Further, many subject-level variables, such as age, sex, genetic polymorphisms, “resiliency,” education, history of early life adversities, parental responsiveness, socioeconomic status, health behaviors, diet, and latent or active viral infections (e.g., cytomegalovirus or herpes virus) may affect LTL, independent of the disease process being studied (Adler et al, 2013; Asok et al, 2013; Aviv et al, 2011; Effros, 2011; Eitan et al, 2014; Epel, 2012; Epel, 2009; Gardner et al, 2014; Gutierrez-Rodrigues et al, 2014; Jacobs et al, 2013; Lung et al, 2005; Nieratschker et al, 2013; Price et al, 2012; Puterman et al, 2013; Puterman et al, 2010; Rizzo et al, 2013; Spyridopoulos et al, 2009; Wikgren et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Note that even in the state of robustness, damage can be already abnormally high (b) and resilience already abnormally low (c) al., 2014). Work is underway to establish an optimal "gold standard" assay for epidemiological studies (Behrens et al, 2017;Montpetit et al, 2014). At this stage, there is not enough evidence in the literature to consider measuring telomere shortening as a biological mechanism of aging or telomere length as a biomarker of biological aging.…”
Section: Of 21mentioning
confidence: 99%
“…Observational studies using these techniques have reported contrasting results, and longitudinal studies have revealed erratic changes over time, possibly due to large measurement error (Berglund et al, ; Bischoff et al, ; Eerola et al, ; Lin et al, ; Müezzinler, Zaineddin, & Brenner, ; Solomon et al, ). Work is underway to establish an optimal “gold standard” assay for epidemiological studies (Behrens et al, ; Montpetit et al, ). At this stage, there is not enough evidence in the literature to consider measuring telomere shortening as a biological mechanism of aging or telomere length as a biomarker of biological aging.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, an increasingly-used assay to measure LTL is the quantitative polymerase chain reaction (81). Other methods for measurement of telomere length include fluorescence in situ hybridization (FISH) and single-telomere analysis (STELA) (83). A reported synchrony between LTL and telomere length in somatic cells of individuals (84) suggests that LTL can serve as a proxy for telomere length in other cell types, such as vascular or cardiac cells.…”
Section: Basic Biology Of Oxidative Stress Ros and Mitochondrial Fumentioning
confidence: 99%